Multi-Omics Insights into Variety-Driven Differences in Rice Straw Feed Utilization: An In Vitro Fermentation Study - Chunrong Zhao; Yuling Kang; Fangbo Cao; Jiana Chen; Huabin Zheng; Weiqin Wang; Min Huang (Fermentation, 2024)
The objective of this study was to explore the rumen fermentation characteristics, bacterial diversity, community composition, and metabolite profiles of rice straw from three distinct varieties. Straws from two hybrid rice varieties, Lingliangyou 268 (L268) and Yueyou 9113 (Y9113), and one inbred rice variety, Zhongzao 39 (Z39), were selected for a 72 h in vitro rumen fermentation test. The fermentation products were analyzed for rumen fermentation characteristics, bacterial community, and rumen metabolomics. The results showed that Y9113 had higher total gas and methane production, greater dry matter digestibility, and higher concentrations of ammonium nitrogen and volatile fatty acids compared to Z39 (p < 0.05). The variety of rice straw did not affect the richness or diversity of the rumen bacterial community (p > 0.05). However, the relative abundances of Verrucomicrobiota, Euryarchaeota, Elusimicrobiota, Probable genus 10, Lachnospiraceae AC2044 group, WCHB1-41, and VadinBE97 were higher in Z39 than in Y9113, while the opposite was observed for Saccharofermentans, UCG-010, and NK4A214 group (p < 0.05). Both principal coordinates analysis (PCoA) and partial least squares discrimination analysis (PLS-DA) revealed clear distinctions in the rumen bacterial communities between Y9113 and Z39. Metabolomic analysis identified eighteen differential metabolites among L268, Z39, and Y9113, with six showing strong correlations with the rumen microbiota. These findings suggest that the feed value of rice straw is influenced by the variety under the same cultivation conditions, due to nutritional disparities that subsequently affect the rumen microbial community and metabolite profiles. This study offers valuable data and insights for the strategic resource utilization of rice straw from different varieties in the livestock industry.